Evaluasi Kinerja Divisi Logistik Berbasis Sistem Pendukung Keputusan dengan Pendekatan OWH-TOPSIS - Ariany, Fenty; Kurniawan, Deny (Jurnal Ilmiah Computer Science, 2025)
The performance of the Logistics Division is one of the important indicators in ensuring the smooth flow of goods, information, and resources in an organization. The optimal performance of the logistics division can be seen from the ability to meet delivery time targets, operational cost efficiency, order fulfillment accuracy, and adaptability to changes in market demand. One of the main problems is that the assessment criteria are not clear or relevant, so the assessment results do not reflect the actual abilities and contributions of employees. In addition, there is a lack of measurable quantitative data to identify operational performance. The solution to this problem involves the application of structured, objective, and data-driven evaluation methods, as well as the development of systems that support transparency in the assessment process. This study aims to evaluate the performance of the Logistics Division objectively and comprehensively using the decision support system approach based on OWH-TOPSIS, so as to provide a transparent, accurate, and relevant performance evaluation system to support strategic decision-making related to improving the performance of the Logistics Division. The results of the ranking of the performance evaluation of the logistics division, Team D showed the best performance with the highest score, which was 0.882. In second place, Team A has a score of 0.8341, followed by Team B with a score of 0.8255. Meanwhile, Team C occupies the last position with the lowest score of 0.6831. This difference in scores indicates that there is a variation in performance between teams, with Team D significantly superior to other teams.